Psychological treatment in female victims of spousal violence - Félix-Montes, Luz Clarita (2020)
The study aimed to identify the therapeutic advances, degree of effectiveness and main clinical manifestations in female victims of spousal violence through literature review. Five online libraries were searched: EBSCOhost, SciELO, ScienceDirect, Redalyc and ProQuest. The inclusion criteria were scientific articles written in Spanish and published worldwide from the year 2000 onwards. It was found that the most commonly used therapies were cognitive behavioral therapy (CBT), rational emotive behavior therapy (REBT) and contextual therapy. Out of these, CBT results showed more evidence of development and effectiveness. The techniques were chosen accordingto the clinical manifestation, lasted from 8 to 20 sessions and were conducted more frequently on an individual basis. Thus, CBT was the most frequently used psychological treatment for battered women due to its efficacy. As a new proposal, contextual therapy was also effective in interventions, but there is no evidence of its widespread use. The most frequently studied clinical manifestations were depression, anxiety, low self-esteem and post-traumatic stress disorder (PTSD). However, this type of studies does not allow to draw generalizable conclusions.